Upadacitinib successfully treats Hailey-Hailey disease: a cases report and literature review - Wu, Zhuochen; Zhu, Qing; Yang, Xu; Xie, Xiaoyu; Zhang, Guoqiang (Frontiers in Immunology, 2026)
Hailey-Hailey disease (HHD) is a rare autosomal dominantly inherited skin disorder first described by brothers Howard and Hugh Hailey in 1939. This article reports a case of refractory Hailey-Hailey disease, which was treated with upadacitinib with remarkable efficacy after the unsatisfactory results of traditional treatment regimens. The patient was a 38-year-old male with a 2-year history of the disease. The rash improved significantly at 3 weeks of oral treatment with upadacitinib 15 mg/day and continued to improve at 12 weeks of follow-up without serious adverse effects. Together with the literature review, this study aims to investigate the efficacy and safety of the JAK inhibitor upadacitinib as a novel therapeutic regimen for Hailey-Hailey disease, and to provide a reference for the clinical treatment of refractory cases.